2014
DOI: 10.1111/bcp.12194
|View full text |Cite
|
Sign up to set email alerts
|

What are validated self-report adherence scales really measuring?: a systematic review

Abstract: AIMSMedication non-adherence is a significant health problem. There are numerous methods for measuring adherence, but no single method performs well on all criteria. The purpose of this systematic review is to (i) identify self-report medication adherence scales that have been correlated with comparison measures of medication-taking behaviour, (ii) assess how these scales measure adherence and (iii) explore how these adherence scales have been validated. METHODSCinahl and PubMed databases were used to search a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
304
0
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 329 publications
(356 citation statements)
references
References 95 publications
(96 reference statements)
6
304
0
15
Order By: Relevance
“…To help improve available information on measures, adherence-related publications should include a clear description of any self-report measure and its administration method, along with descriptive data resulting from the measure (e.g., mean, median, standard deviation) [9,35]. Define the adherence construct you want to assess-It is important to define the specific construct of interest when conducting medication adherence assessments and to select an appropriately corresponding measure [7,52,59,60]. Voils and colleagues [12,52,61] have argued that self-report adherence measures often conflate two distinct constructs-the extent of nonadherence and reasons for nonadherence-and this conflation may be one factor that has limited the psychometric properties and validity of many existing self-report measures.…”
Section: Recommendations For Optimizing the Validity Of Self-report Mmentioning
confidence: 99%
See 4 more Smart Citations
“…To help improve available information on measures, adherence-related publications should include a clear description of any self-report measure and its administration method, along with descriptive data resulting from the measure (e.g., mean, median, standard deviation) [9,35]. Define the adherence construct you want to assess-It is important to define the specific construct of interest when conducting medication adherence assessments and to select an appropriately corresponding measure [7,52,59,60]. Voils and colleagues [12,52,61] have argued that self-report adherence measures often conflate two distinct constructs-the extent of nonadherence and reasons for nonadherence-and this conflation may be one factor that has limited the psychometric properties and validity of many existing self-report measures.…”
Section: Recommendations For Optimizing the Validity Of Self-report Mmentioning
confidence: 99%
“…Stated simply, self-reports of nonadherence can be trusted; self-reports of adherence less so. Osterberg and Blaschke [10] explained that Ba patient who admits to poor adherence is generally being candid. review of self-report measures found that only 12 of 43 scales reported sensitivity and specificity data [7]. Sensitivity and specificity may be infrequently calculated because it requires comparison with a Bgoldstandard^clinical outcome or adherence measure, as well as establishment of an appropriate cut-off for determining nonadherence-and there is lack of 1.…”
Section: Practice and Public Health Policiesmentioning
confidence: 99%
See 3 more Smart Citations